Impact of Wuhan lockdown on the indications of cesarean delivery and newborn weights during the epidemic period of COVID-19 - Li, Min (PLoS One, 2020)
OBJECTIVE: To prevent the rapid spread of COVID-19, the Chinese government implemented a strict lockdown in Wuhan starting on 23 January, 2020, which inevitably led to the changes in indications for the mode of delivery. In this retrospective study, we present the changes in the indications for cesarean delivery (CD) and the birth weights of newborns after the lockdown in Wuhan. METHODS: A total of 3,432 pregnant women in the third trimester of their pregnancies who gave birth in our hospital from 23 January 2019 to 24 March 2020 were selected as the observation group, while 7,159 pregnant women who gave birth from 1 January 2019 to 22 January 2020 were selected as the control group; control group was matched using propensity score matching (PSM). A comparative analysis of the two groups was performed with the chi-square test, t test and rank sum test. RESULTS: The difference in the overall rate of CD between the two groups was not statistically significant (p<0.05). Among the indications for CD, CD on maternal request (CDMR) and fetal distress were also significantly more common in the observation group (p<0.05) than the control group. Furthermore, we found that the weight of newborns was significantly heavier in the observation group than in the control group when considering full-term or close-to-full-term births (p<0.05). CONCLUSIONS: The results may provide useful information to management practices regarding pregnancy and childbirth after lockdown in other cities or countries, enabling better control of the rate of CD due to CDMR, reducing fetal distress, and controlling newborn weight. We recommend that pregnant women pay more attention to controlling the weight of newborns through diet and exercise.